High‐Performance Blue OLEDs Based on Phenanthroimidazole Emitters via Substitutions at the C6‐ and C9‐Positions for Improving Exciton Utilization. Issue 34 (14th July 2016) - Liu, Bin; Yuan, Yi; He, Dan; Huang, De‐Yue; Luo, Cheng‐Yuan; Zhu, Ze‐Lin; Lu, Feng; Tong, Qing‐Xiao; Lee, Chun‐Sing
Abstract: Donor–acceptor (D–A) molecular architecture has been shown to be an effective strategy for obtaining high‐performance electroluminescent materials. In this work, two D–A molecules, Ph‐BPA‐BPI and Py‐BPA‐BPI, have been synthesized by attaching highly fluorescent phenanthrene or pyrene groups to the C6‐ and C9‐positions of a locally excited‐state emitting phenylamine–phenanthroimidazole moiety. Equipped with good physical and hybridized local and charge‐transfer properties, both molecules show high performances as blue emitters in nondoped organic light‐emitting devices (OLEDs). An OLED using Ph‐BPA‐BPI as the emitting layer exhibits deep‐blue emission with CIE coordinates of (0.15, 0.08), and a maximum external quantum efficiency (EQE), current efficiency (CE), and power efficiency (PE) of 4.56 %, 3.60 cd A −1, and 3.66 lm W −1, respectively. On the other hand, a Py‐BPA‐BPI‐based, sky‐blue OLED delivers the best results among nondoped OLEDs with CIE y values of < 0.3 reported so far, for which a very low turn‐on voltage of 2.15 V, CIE coordinates of (0.17, 0.29), and maximum CE, PE, and EQE values of 10.9 cd A −1, 10.5 lm W −1, and 5.64 %, were achieved, respectively. More importantly, both devices show little or even no efficiency roll‐off and high singlet exciton‐utilizing efficiencies of 36.2 % for Ph‐BPA‐BPI and 39.2 % for Py‐BPA‐BPI. Abstract : Out of the blue : TwoD –A molecules, Ph‐BPA‐BPI and Py‐BPA‐BPI, have been synthesized by introducing functional groups to the C6‐ and C9‐positions of a phenanthroimidazole unit (see figure). The non‐doped blue OLEDs based on them exhibit impressive performances with a high exciton‐utilizing efficiency of 36.2 % for Ph‐BPA‐BPI and 39.2 % for Py‐BPA‐BPI.